Application of coffee husk compost and EM4 on growth and yield of chili pepper (Capsicum Frutescens L.). Issue 4 (July 2021) - Adnan; Basri, A B; Azis, Abdul; Idawanni; Iswoyo, H
Abstract: This research is intended to comprehend the effect of using waste from coffee husk and EM4 concentration on the growth and yield of chili pepper plants with two factors and repeating 3 times. The research starts from October 2018 to January 2019 by using a factorial randomized block design (RBD), which consisted of two factors namely: The factor of coffee husk waste (K) consisting of 4 levels, while the factor of EM4 concentration consist 4 levels. The research results prove that the waste of coffee husk has a significant impact on the number of productive branches, the number of fruits per plant, and fruit weight per plot. It significantly affects plant height at 45 days after planting (DAP) and stems diameter at 45 days after planting (DAP). The best treatment of coffee husk compost is found in K3 treatment (30 ton/ha). The treatment of EM4 concentration has a good effect on the number of productive branches, the number of fruits per plant, and fruit weight per plot. The best EM4 concentration treatment is found in the B3 treatment (15 mL/L water). The interaction between the coffee husk waste and the EM4 concentration confirms a significant effect on fruit weight per plot. The finest interaction is found in the compost of coffee husk waste 30 ton/ha with a concentration of EM4 15 mL/L water.